GENETIC DIVERSITY OF LOCAL GRAPE VARIETIES AND POSSIBILITIES OF THEIR APPLICATION IN BREEDING - Dadabayeva Ozodakhon Savriddin kizi (Innovate Conferences, 2025)
In this study, the genetic diversity of local grape varieties (Husayni, Toyfi, Kattakurgan, Kara Kishmish, Rizamat) widespread in Uzbekistan was studied and their potential for use in the selection process was analyzed. Using molecular markers (SSR, AFLP, SNP), the genetic distance between varieties was determined, and their similarities and differences were noted. The results showed that although local varieties have high yield and quality characteristics, they have a relatively low level of disease resistance. It was confirmed that resistance genes are more common in foreign varieties. The possibility of creating new genetic combinations and increasing selection efficiency by crossing these two groups was scientifically substantiated. Also, the preservation of genetic resources of local varieties, their passporting and their introduction into international selection programs were assessed as an important factor for the sustainable development of the Uzbek viticulture sector.
Keywords: Grape varieties, genetic diversity, local gene pool, molecular marker, selection, hybridization, disease resistance, agrobiological properties.